Determinants of orchid species diversity in Latin America - Štípková, Zuzana; Traxmandlová, Iva; Kindlmann, Pavel (Lankesteriana: International Journal on Orchidology, 2016)
Area and latitude are thought to be the most important determinants of species richness. The relative importance of these two factors was recently tested, using data on orchid species diversity in various countries in the world and it was found that size of the country (or of the protected areas within the country) is a better determinant of species diversity in orchids than latitude. On the other hand, literature data indicate that in many groups species richness is also heavily dependent on habitat diversity as expressed by the range of altitudes in the region considered. Here we analyze the species richness data for various countries in Latin America, using the above-mentioned altitudinal amplitude as a proxy. Habitat diversity played a role in tropical, but not in temperate countries. The reason may indicate that in the temperate countries only few orchid species grow in higher elevations, so an increase of altitudinal range of habitats there does not entail a corresponding increase of species richness there. Thus, especially in the tropics, efforts should be directed to preservation of protected areas in all altitudes, rather than to increase of existing reserve size only in areas that are not attractive for human development.